A qualitative study of midwives’ perceptions on using video-calling in early labor - Spiby, Helen; Faucher, Mary Ann; Sands, Gina; Roberts, Julie; Kennedy, Holly Powell (Wiley, 2018)
BACKGROUND: Decisions made in early labor influence the outcomes of childbirth for women and infants. Telephone assessment during labor, the current norm in many settings, has been found to be a source of dissatisfaction for women and can present challenges for midwives. The aim of this qualitative study was to explore midwives’ views on the potential of video-calling as a method for assessing women in early labor. METHODS: A series of eight midwife focus groups (n=45) and interviews (n=4) in the Midlands region of England and the mid-South and Northeast regions of the United States were completed. Audio recordings were transcribed verbatim and coded using content analysis. Coding diagrams were used to help develop major themes in the data. Audio recordings were transcribed verbatim and coded using content analysis. Coding diagrams were used to help develop major themes in the data. RESULTS: Midwives were generally positive about the potential of video-calling in early labor and using visual cues to make more accurate assessments and to enhance trust. Some midwives expressed concerns about privacy, both for themselves and for women, and issues of accessibility. They suggested strategies for implementation and further research, such as the need for a private space in birth facilities and training for both staff and service users. CONCLUSIONS: Video-calling was seen as a viable option for assessment of women in early labor with some particular challenges related to implementation. This research focused on midwives’ views; the views of women and their families should also be considered. There is a lack of evidence on the clinical and cost effectiveness of video-calling in maternity care and further research is warranted.